Preparation method of perovskite-based ink
By preparing the osteotic ink and heat treatment at low temperature, the problem of high energy consumption and material restrictions caused by high temperature annealing in existing technologies has been solved, and the low energy consumption preparation of the lymph and lymphaosted light activity layer has been realized, which has expanded its expansion. Scope of application.
Patent Information
- Application Number
- CN202380047635.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-09
- Filing Date
- 2023-08-02
- Publication Date
- 2025-01-28
AI Technical Summary
The prior art When preparing perovskite-based photovoltaic cells, high-temperature annealing is required to stabilize the photoactive layer of cesium lead triiodide (CsPbI3), resulting in high energy consumption and material limitations, making it difficult to widely use in industrial fields and flexible electronic devices.
By preparing the oretic ink ink, use iodide, lead iodide, dihydrax iodide (DMAI), and dihydramium bromide (DMABR) as the forefront material to control the Moore of the ammonium salt. Between 0: 100 and 50:50, heat treatment is performed below 210 ° C to form a stable perovskite light activity layer.
The stabilization of ostellet lytic activity layer at a lower temperature has been achieved, reducing energy consumption, and expanding its application potential in the industrial field and flexible electronic devices.
Smart Images

Figure CN119384893A_ABST
Abstract
Description
[0001] The present invention relates to a method for preparing perovskite-based ink.
[0002] More specifically, the present invention relates to a method for preparing a perovskite-based ink, wherein the perovskite has the general formula (I):
[0003] PcqI 3-y Br y (I)
[0004] wherein y is a number from 0 to 0.2, preferably from 0.05 to 0.1, wherein a solution of a precursor of the perovskite is used, the precursor of the perovskite comprising cesium iodide, lead iodide, at least one ammonium salt having the general formula (II) reported below and at least one ammonium salt having the general formula (III) reported below, the at least one ammonium salt having the general formula (II) and the at least one ammonium salt having the general formula (III) being used in a molar ratio of 0:100 to 50:50.
[0005] The perovskite-based inks can be advantageously used in optoelectronic applications, in particular in perovskite-based photovoltaic cells (or solar cells), light emitting diodes (LEDs), X-ray sensors, photodetectors.
[0006] The present invention also relates to a method for preparing a perovskite-based film, comprising the following steps: (i) depositing the perovskite-based ink obtained according to the method object of the present invention on a substrate to form a film; (ii) heat treating (annealing) the substrate at a temperature of 120°C to 190°C, preferably 135°C to 185°C.
[0007] In recent years, the need to reduce carbon dioxide (CO2) emissions for sustainable development has made photovoltaics (or solar energy) a leading alternative energy solution to fossil fuels. However, today's market is dominated by solutions that are low-cost and highly efficient, but require energy-intensive manufacturing methods with high energy consumption. To this end, research is focusing on developing new semiconductor materials that are efficient, low-cost, and have a low environmental impact.
[0008] In particular, the last decade has seen the emergence of new semiconductor materials based on hybrid organic-inorganic compounds known as hybrid perovskites. Hybrid perovskites (more general in the class of organic-inorganic hybrid perovskites and historically typified by methylammonium lead triiodide (CH3NH3PbI3)) possess excellent optoelectronic properties, including high absorption coefficients, the possibility of easily tunable band gaps, tolerance to structural defects, and high diffusion lengths for charge carriers.
[0009] Photovoltaic cells (or solar cells) based on organic-inorganic hybrid perovskites have shown exponential growth in energy conversion efficiency (PCE), reaching values of 25.6% in the case of single-junction photovoltaic cells (or solar cells), a value that surpasses more established photovoltaic (or solar) technologies. These hybrid perovskite-based photovoltaic cells (or solar cells) consist of a series of stacked thin layers, in which the organic-inorganic perovskite is inserted between two charge transport layers: a layer based on a hole transport material (HTL) and a layer based on an electron transport material (ETL). At opposite ends of these hybrid perovskite-based photovoltaic cells (or solar cells), we find a glass substrate covered with a transparent conductive oxide on one side and a metal contact, known as a back contact, on the opposite side.
[0010] Another class of perovskites suitable for use in optoelectronic devices and photovoltaics (or solar energy) is the inorganic perovskite (in which the organic part is replaced by an inorganic element such as cesium (Cs)). Compared to mixed perovskites, these materials exhibit enhanced thermal stability, primarily due to the absence of volatile and hygroscopic organic cations. Among the main materials belonging to this class, cesium lead triiodide (CsPbI3) has been developed. When used in the photoactive layer of photovoltaic (or solar) cells in the so-called "direct" configuration, it allows achieving energy conversion efficiency values [power conversion efficiency - (PCE)] exceeding 20%, which can be appropriately adjusted by inserting additional layers. However, a significant limitation to the use of this material is the high annealing temperature to which the photoactive layer containing it is subjected: this is not only an energy-intensive process, but also limits the application of cesium lead triiodide (CsPbI3) within photovoltaic cells (or solar cells). In fact, the layer based on electron transport materials (electron transport layer - ETL) located below the photoactive layer comprising cesium lead triiodide (CsPbI3) must be able to withstand without degradation the temperature of 210°C, the temperature most commonly used for the thermal treatment (annealing) of said photoactive layer.
[0011] Photovoltaic cells (or solar cells) are divided into two categories, photovoltaic cells in direct configuration or "nip" configuration and photovoltaic cells in inverted configuration or "pin" configuration.
[0012] A photovoltaic cell in a direct configuration or "nip" configuration is a photovoltaic cell having a layer based on an electron transport material (electron transport layer - ETL) located below a photoactive layer comprising a perovskite, with a layer based on a hole transport material (hole transport layer - HTL) placed above the photoactive layer. In contrast, in an inverted configuration or "pin" cell, the layer below the photoactive layer comprising a perovskite is a layer based on a hole transport material (hole transport layer - HTL), while the layer above the photoactive layer is a layer based on an electron transport material (electron transport layer - ETL).
[0013] Typically, photovoltaic cells (or solar cells) with a photoactive layer comprising cesium lead triiodide (CsPbI3) reported in the literature are photovoltaic cells with a direct configuration or "nip" configuration, more specifically comprising the following layers: (i) a glass substrate covered with a transparent conductive oxide layer (transparent conductive oxide - TCO); (ii) a layer based on an electron transport material (electron transport layer - ETL), typically a dense layer of titanium dioxide (c-TiO2); (iii) optionally, a mesoporous titanium dioxide (TiO2) scaffold, the purpose of which is to provide a larger interface area with the perovskite by increasing the electron collection efficiency; (iv) a photoactive layer comprising cesium lead triiodide (CsPbI3); (v) a layer based on a hole transport material (hole transport layer - HTL), typically spiro-OMeTAD (N-OMeTAD) ... 2 ,N 2 ,N 2′ ,N 2′ ,N 7 ,N 7 ,N 7′ ,N 7′ -octa(4-methoxyphenyl)-9,9′-spirobi[9H-fluorene]-2,2′,7,7′-tetramine) layer; (vi) a metal contact, called the back contact, which constitutes the cathode and is usually a metal layer of gold, silver or copper. To protect them from atmospheric factors and to enable their use under practical conditions, these photovoltaic cells (or solar cells) are usually encapsulated with glass.
[0014] Cesium lead triiodide (CsPbI3) has four crystalline phases, divided into two main groups. The first group, the so-called black phases, consists of the cubic phase denoted by the Greek letter α, the tetragonal β phase, and the orthorhombic γ phase. These phases have a band gap of approximately 1.7 eV and are suitable for use as active materials in perovskite-based photovoltaic cells (or solar cells); for this reason, they are often referred to as photoactive phases. The second group, on the other hand, consists of the so-called yellow phase denoted by the Greek letter δ, which belongs to the orthorhombic system and has a band gap of 2.95 eV. Due to its high band gap, it is not used in perovskite-based photovoltaic cells (or solar cells).
[0015] Methods for depositing one of the above-mentioned photoactive phases of cesium lead triiodide (CsPbI3) are known in the art.
[0016] Typically, the deposition method of cesium lead triiodide (CsPbI3) is performed by spin coating a precursor solution of cesium lead triiodide (CsPbI3), which is prepared by dissolving lead iodide (PbI2) and cesium iodide (CsI) in an organic solvent such as dimethylformamide (DMF) and dimethyl sulfoxide (DMSO). The thin film obtained after deposition must be heat treated (annealed) to remove the solvent and allow the nucleation of cesium lead triiodide (CsPbI3) grains. In order to obtain higher performance photovoltaic cells (or solar cells), hydrogen iodide (HI) is usually added to the mixture of lead iodide (PbI2) and cesium iodide (CsI). Hydrogen iodide reacts with dimethylformamide (DMF) by hydrolyzing dimethylformamide (DMF) and forming dimethylammonium iodide (DMAI). This compound (added to the mixture or synthesized in situ in a suitable amount) allows the deposition and stabilization of the beta phase of cesium lead triiodide (CsPbI3), which allows cells in direct configuration to achieve efficiencies higher than 16%. The thin film obtained from the deposition of the mixture is then subjected to a heat treatment (annealing) at 210°C for 5 minutes: this heat treatment (annealing) allows the conversion of the dissolved precursors into dimethylammonium lead triiodide (DMAPbI3) and cesium lead hexaiodide (Cs4PbI6), a low-dimensional perovskite. Subsequently, due to the high temperature of the heat treatment (annealing), these two compounds combine to form cesium lead triiodide (CsPbI3), while removing dimethylammonium iodide (DMAI) in gaseous form (see Scheme 1 below):
[0017] Solution 1
[0018] CsI+PbI2+xDMAI→DMAPbI3+Cs4PbI6→CsPbI3+DMAI
[0019] More details about the above method can be found in, for example, the following articles: Whang Y. et al., “Angewante Chemie” (2019), Vol. 58, No. 46, pp. 16691-16696 and Wang H. et al., in “NanoEnergy” (2021), Vol. 84, 105881.
[0020] As mentioned above, perovskite-based photovoltaic cells (or solar cells) with a photoactive layer comprising cesium lead triiodide (CsPbI3) are photovoltaic cells with a direct configuration or "nip" configuration, in which the layer based on a hole transport material (hole transport layer - HTL) is typically spiro-OMeTAD (N 2 ,N 2 ,N2′ ,N 2′ ,N 7 ,N 7 ,N 7′ ,N 7′ -octa(4-methoxyphenyl)-9,9′-spirobi[9H-fluorene]-2,2′,7,7-tetramine) layer and the layer based on the electron transport material (electron transport layer -ETL) is usually a dense layer of titanium dioxide (c-TiO2). One of the reasons for choosing a dense layer of titanium dioxide (c-TiO2) as an electron carrier is that it can withstand temperatures of 210°C without degrading its optoelectronic properties.
[0021] However, the need to use energy-intensive methods, such as heat treatment (annealing) at high temperatures (i.e. 210°C) to stabilize the photoactive phase of cesium lead triiodide (CsPbI3), limits the use of said perovskites in the industrial sector and in applications requiring lower processing temperatures, such as flexible electronics. Furthermore, it should be remembered that in perovskite-based photovoltaic cells (or solar cells) with a photoactive layer comprising cesium lead triiodide (CsPbI3) in a direct or "nip" configuration, the material most commonly used for the layer based on an electron transport material (electron transport layer - ETL) is titanium dioxide (TiO2), which, however, requires a heat treatment (annealing) at 450°C to stabilize the phase suitable for electron transport: a process that is particularly expensive and difficult to apply in the industrial sector.
[0022] Therefore, in order to overcome the drawbacks reported above, the development of a method that allows stabilization of the black phase at lower temperatures for the deposition of cesium lead triiodide (CsPbI3) layers could create the conditions for the use of alternative electron transport materials such as tin oxide (SnO2) (if the direct configuration or "nip" configuration is considered) or hole transport materials such as the acid [2-(3,6-dimethoxy-9H-carbazol-9-yl)ethyl]phosphonic acid (MeO-2PACz) (if the inverted configuration or "pin" configuration is considered), which is carried out at low temperatures and therefore allows better application in the industrial field and in applications such as flexible electronic devices.
[0023] The Applicant therefore addressed the problem of finding a method for preparing perovskite-based inks, wherein the perovskite is cesium lead triiodide (CsPbI 3 ), which allows stabilization of its photoactive phase at lower temperatures than those usually used.
[0024] The applicant has discovered a method for preparing a perovskite-based ink, wherein the perovskite is cesium lead triiodide (CsPbI3), wherein the precursor solution of the cesium lead triiodide (CsPbI3) contains cesium iodide, lead iodide, dimethylammonium iodide (DMAI) and dimethylammonium bromide (DMABr), and the dimethylammonium iodide (DMAI) and dimethylammonium bromide (DMABr) are used in a molar ratio of 0:100 to 50:50. The perovskite-based film obtained by the method is heat-treated (annealed) at a temperature below 210°C to obtain a photoactive perovskite phase, thereby allowing better application in industrial fields and applications such as flexible electronic devices. The perovskite-based ink can be advantageously used in optoelectronic applications, in particular in perovskite-based photovoltaic cells (or solar cells), light-emitting diodes (LEDs), X-ray sensors, and photodetectors.
[0025] The object of the present invention is therefore a process for preparing perovskite-based inks, said perovskite having the general formula (I):
[0026] PcqI 3-y Br y (I)
[0027] wherein y is a number from 0 to 0.2, preferably from 0.05 to 0.1;
[0028] The following steps are involved:
[0029] (a) dissolving lead iodide (PbI2) in at least one organic solvent selected from dimethyl sulfoxide (DMSO), dimethylformamide (DMF), γ-butyrolactone (GBL), γ-valerolactone (GVL) or a mixture thereof, preferably dimethyl sulfoxide (DMSO), dimethylformamide (DMF) or a mixture thereof to obtain a first solution;
[0030] (b) dissolving cesium iodide (CsI) and at least one ammonium salt having the general formula (II) in a portion of the first solution obtained in step (a) to obtain a second solution:
[0031] R x H 4-x NI(II)
[0032] wherein R represents a linear or branched C1-C4 alkyl group, preferably a methyl group, and x is an integer from 2 to 4, preferably 2;
[0033] (c) dissolving cesium iodide (CsI) and at least one ammonium salt having the general formula (III) in a portion of the first solution obtained in step (a) to obtain a third solution:
[0034] R x H 4-xNBr(III)
[0035] wherein R represents a linear or branched C1-C4 alkyl group, preferably a methyl group, and x is an integer from 2 to 4, preferably 2;
[0036] (d) mixing the second solution obtained in step (b) with the third solution obtained in step (c) to obtain a perovskite-based ink;
[0037] Characterized in that, in the step (d), the molar ratio of the at least one ammonium salt having the general formula (II) to the at least one ammonium salt having the general formula (III) is 0:100 to 50:50.
[0038] For the purposes of the present description and of the following claims, the definitions of numerical ranges always include the extreme values, unless otherwise indicated.
[0039] For the purposes of this specification and the following claims, the term "comprising" also encompasses the terms "consisting essentially of or "consisting of.
[0040] According to a preferred embodiment of the present invention, the at least one ammonium salt having the general formula (II) is dimethylammonium iodide (DMAI).
[0041] According to a preferred embodiment of the present invention, the at least one ammonium salt of the general formula (III) is dimethylammonium bromide (DMABr).
[0042] According to a preferred embodiment of the present invention, the step (a) may be performed at a temperature of 30°C to 80°C, preferably 40°C to 70°C.
[0043] According to a preferred embodiment of the present invention, step (a) may be performed for 1 to 12 hours, preferably 4 to 11 hours.
[0044] According to a preferred embodiment of the present invention, the step (b) may be performed at a temperature of 15°C to 35°C, preferably 20°C to 30°C, more preferably at room temperature (25°C).
[0045] According to a preferred embodiment of the present invention, the step (b) can be performed for 5 minutes to 2 hours, preferably 10 minutes to 1 hour.
[0046] According to a preferred embodiment of the present invention, the step (c) may be performed at a temperature of 15°C to 35°C, preferably 20°C to 30°C, more preferably at room temperature (25°C).
[0047] According to a preferred embodiment of the present invention, step (c) may be performed for 5 minutes to 2 hours, preferably 10 minutes to 1 hour.
[0048] According to a preferred embodiment of the present invention, the step (d) may be performed at a temperature of 15°C to 35°C, preferably 20°C to 30°C, more preferably at room temperature (25°C).
[0049] According to a preferred embodiment of the present invention, step (d) may be performed for 5 minutes to 2 hours, preferably 8 minutes to 1 hour.
[0050] The present invention also relates to a method for preparing a perovskite film, comprising the following steps: (i) depositing the perovskite-based ink obtained according to the method object of the present invention on a substrate to form a film; (ii) heat treating (annealing) the substrate at a temperature of 120°C to 190°C, preferably 135°C to 185°C.
[0051] The deposition of the perovskite-based ink on the substrate can be performed according to deposition techniques known in the art, such as spin coating, slot coating, doctor blade coating, screen printing, spray coating, inkjet printing, gravure printing, spray pyrolysis.
[0052] As mentioned above, the perovskite-based ink obtained by the method object of the present invention can be advantageously used in perovskite-based photovoltaic cells (or solar cells).
[0053] Therefore, another object of the present invention is a method for preparing a perovskite-based photovoltaic cell (or solar cell), comprising the following steps:
[0054] (a1) preparing a glass substrate covered with a transparent conductive oxide layer (transparent conductive oxide-TCO) (anode) [e.g., an indium tin oxide layer (indium tin oxide-ITO) or a fluorine-doped tin oxide (SnO2:F) layer (fluorine-doped tin oxide-FTO)];
[0055] (b1) depositing a layer based on an electron transport material (electron transport layer - ETL) (e.g., a dense layer of titanium dioxide (c-TiO2)) on the photoactive layer obtained in step (a1);
[0056] (c1) optionally, depositing a layer based on a mesoporous oxide (scaffold) on the layer based on an electron transport material (electron transport layer - ETL) obtained in step (b1);
[0057] (d1) depositing the perovskite-based ink obtained according to the method object of the present invention on the layer based on electron transport material (electron transport layer - ETL) obtained in said step (b1), or on the layer based on mesoporous oxide (scaffold) obtained in said step (c1), so as to obtain a photoactive layer;
[0058] (e1) depositing a layer based on a hole transport material (hole transport layer - HTL) (e.g. spiro-OMeTAD (N 2 ,N 2 ,N 2′ ,N 2′ ,N 7 ,N 7 ,N 7′ ,N 7′ -octa(4-methoxyphenyl)-9,9′-spirobi[9H-fluorene]-2,2′,7,7′-tetramine) layer);
[0059] (f1) depositing a metal contact, called back contact, constituting the cathode (for example, a metal layer of gold, silver or copper, or a layer of a graphene derivative, for example a layer of silver nanowires) on the layer based on a hole transport material (hole transport layer—HTL) obtained in said step (e1);
[0060] Wherein said step (d1) is carried out at a temperature of 120°C to 190°C, preferably 135°C to 185°C.
[0061] For the purpose of the above method, steps (b1), (c1), (d1) and (e1) can be carried out according to deposition techniques known in the art, such as spin coating, slit coating, doctor blade coating, screen printing, spray coating, inkjet printing, gravure printing, spray pyrolysis.
[0062] For the purpose of the above method, said step (f1) can be performed according to techniques known in the art, such as evaporation, sputtering, electron beam assisted deposition, sputtering, spin coating, gravure printing, flexographic printing, slot coating.
[0063] Reference will now be made to the following report Figure 1 , the present invention is described in more detail through embodiments.
[0064] Specifically, Figure 1 A cross-sectional view (1) of a perovskite-based photovoltaic cell (or solar cell) in a direct or "nip" configuration is shown, comprising the following layers: a glass substrate (7) covered by a transparent conductive oxide layer (transparent conductive oxide - TCO) (anode) [e.g. indium tin oxide (indium tin oxide - ITO) or fluorine-doped tin oxide (SnO2:F) (fluorine-doped tin oxide - FTO)] (2); a layer based on an electron transport material (electron transport layer - ETL) (e.g. a dense layer of titanium dioxide (c-TiO2)) (3); and optionally a scaffold of mesoporous titanium dioxide (TiO2) with the purpose of providing a larger interface area with the perovskite by increasing the electron collection efficiency ( Figure 1); a photoactive layer (4) comprising a perovskite-based ink obtained by the method targeted by the present invention; a layer based on a hole transport material (hole transport layer - HTL) [e.g., spiro-OMeTAD (N 2 ,N 2 ,N 2′ ,N 2′ ,N 7 ,N 7 ,N 7′ ,N 7′ -octa(4-methoxyphenyl)-9,9′-spirobi[9H-fluorene]-2,2′,7,7′-tetramine) layer] (5); a metal contact called a back contact [a metal layer such as gold, silver or aluminum] (6) constituting the cathode.
[0065] In order to better understand the invention and to put it into practice, some illustrative and non-limiting examples of the invention are reported below.
[0066] In the following embodiments, for the sake of simplicity, the term solar cell is used, which should be understood to have the same meaning as a photovoltaic cell.
[0067] Example 1 (comparison)
[0068] Preparation of perovskite containing dimethylammonium iodide (DMAI) and dimethylammonium bromide (DMABr) in a molar ratio of 75:25 Mineral-based inks
[0069] 655 mg of lead iodide (TCI-Tokyo Chemical Industries) (1.421 mol) and 1.4764 mL of a mixture of dimethylformamide (DMF) (Merck) and dimethyl sulfoxide (DMSO) (Merck) in a ratio of 4:1 (v / v) were introduced into a 4 mL vial: the resulting solution was stirred on a hot plate at a temperature of 60° C. for 10 hours to obtain a first solution. Subsequently, 112 mg of cesium iodide (TCI-Tokyo Chemical Industries) (0.431 mol) and 74.6 mg of dimethylammonium iodide (DMAI) (Merck) (0.431 mol) previously weighed in a 1.5 mL vial, as well as 479 μL of the first solution, were introduced into a 4 mL vial: the resulting solution was stirred on a plate at room temperature (25° C.) for 30 minutes to obtain a second solution. Subsequently, 237 mg of cesium iodide (TCI-Tokyo Chemical Industries) (0.912 mol) and 80.5 mg of dimethylammonium bromide (DMABr) (Greatcell Solar Materials) (0.639 mol) previously weighed in a 1.5 mL vial, along with 1.0136 mL of the first solution, were introduced into a 4 mL vial. The resulting solution was stirred on a plate at room temperature (25° C.) for 30 minutes to obtain a third solution. Subsequently, 267 μL of the second solution containing dimethylammonium iodide (DMAI) and 127.2 μL of the third solution containing dimethylammonium bromide (DMABr) were introduced into a 4 mL vial. The whole was mixed using a magnetic stirrer at room temperature (25° C.) for 10 minutes to obtain a perovskite-based ink containing dimethylammonium iodide (DMAI) and dimethylammonium bromide (DMABr) in a molar ratio of 75:25.
[0070] Example 2 (Invention)
[0071] Preparation of perovskite containing dimethylammonium iodide (DMAI) and dimethylammonium bromide (DMABr) in a molar ratio of 50:50 Mineral-based inks
[0072] 655 mg of lead iodide (TCI-Tokyo Chemical Industries) (1.421 mol) and 1.4764 mL of a mixture of dimethylformamide (DMF) (Merck) and dimethyl sulfoxide (DMSO) (Merck) in a ratio of 4:1 (v / v) were introduced into a 4 mL vial: the resulting solution was stirred on a hot plate at a temperature of 60° C. for 10 hours to obtain a first solution. Subsequently, 112 mg of cesium iodide (TCI-Tokyo Chemical Industries) (0.431 mol) and 74.6 mg of dimethylammonium iodide (DMAI) (Merck) (0.431 mol) previously weighed in a 1.5 mL vial, as well as 479 μL of the first solution, were introduced into a 4 mL vial: the resulting solution was stirred on a plate at room temperature (25° C.) for 30 minutes to obtain a second solution. Subsequently, 237 mg of cesium iodide (TCI-Tokyo Chemical Industries) (0.912 mol) and 80.5 mg of dimethylammonium bromide (DMABr) (Greatcell Solar Materials) (0.639 mol) previously weighed in a 1.5 mL vial, and 1.0136 mL of the first solution were added to a 4 mL vial: the obtained solution was stirred on a plate at room temperature (25° C.) for 30 minutes to obtain a third solution. Subsequently, 161.6 μL of the second solution containing dimethylammonium iodide (DMAI) and 230.9 μL of the third solution containing dimethylammonium bromide (DMABr) were introduced into a 4 mL vial: the whole was mixed by a magnetic stirrer at room temperature (25° C.) for 10 minutes to obtain a perovskite-based ink containing dimethylammonium iodide (DMAI) and dimethylammonium bromide (DMABr) in a molar ratio of 50:50.
[0073] Example 3 (present invention)
[0074] Preparation of perovskite containing dimethylammonium iodide (DMAI) and dimethylammonium bromide (DMABr) in a molar ratio of 25:75 Mineral-based inks
[0075] 655 mg of lead iodide (TCI-Tokyo Chemical Industries) (1.421 mol) and 1.4764 mL of a mixture of dimethylformamide (DMF) (Merck) and dimethyl sulfoxide (DMSO) (Merck) in a ratio of 4:1 (v / v) were introduced into a 4 mL vial: the resulting solution was stirred on a hot plate at a temperature of 60° C. for 10 hours to obtain a first solution. Subsequently, 112 mg of cesium iodide (TCI-Tokyo Chemical Industries) (0.431 mol) and 74.6 mg of dimethylammonium iodide (DMAI) (Merck) (0.431 mol) previously weighed in a 1.5 mL vial, as well as 479 μL of the first solution, were introduced into a 4 mL vial: the resulting solution was stirred on a plate at room temperature (25° C.) for 30 minutes to obtain a second solution. Subsequently, 237 mg of cesium iodide (TCI-Tokyo Chemical Industries) (0.912 mol) and 80.5 mg of dimethylammonium bromide (DMABr) (Greatcell Solar Materials) (0.639 mol) previously weighed in a 1.5 mL vial, and 1.0136 mL of the first solution were added to a 4 mL vial: the obtained solution was stirred on a plate at room temperature (25° C.) for 30 minutes to obtain a third solution. Subsequently, 73.6 μL of the second solution containing dimethylammonium iodide (DMAI) and 315.4 μL of the third solution containing dimethylammonium bromide (DMABr) were introduced into a 4 mL vial: the whole was mixed by a magnetic stirrer at room temperature (25° C.) for 10 minutes to obtain a perovskite-based ink containing dimethylammonium iodide (DMAI) and dimethylammonium bromide (DMABr) in a molar ratio of 25:75.
[0076] Example 4 (present invention)
[0077] Preparation of perovskite containing dimethylammonium iodide (DMAI) and dimethylammonium bromide (DMABr) in a molar ratio of 0:100 Mineral-based inks
[0078] 655 mg of lead iodide (TCI-Tokyo Chemical Industries) (1.421 mol) and 1.4764 mL of a mixture of dimethylformamide (DMF) (Merck) and dimethyl sulfoxide (DMSO) (Merck) in a ratio of 4:1 (v / v) were introduced into a 4 mL vial: the obtained solution was stirred on a hot plate at a temperature of 60° C. for 10 hours to obtain a first solution. Subsequently, 237 mg of cesium iodide (TCI-Tokyo Chemical Industries) (0.912 mol) and 80.5 mg of dimethylammonium bromide (DMABr) (Greatcell Solar Materials) (0.639 mol) previously weighed in a 1.5 mL vial and 1.0136 mL of the first solution were added to a 4 mL vial: the obtained solution was stirred on a plate at room temperature (25° C.) for 30 minutes to obtain a perovskite-based ink containing dimethylammonium iodide (DMAI) and dimethylammonium bromide (DMABr) in a molar ratio of 0:100.
[0079] Example 5 (comparative)
[0080] Preparation of perovskite containing dimethylammonium iodide (DMAI) and dimethylammonium chloride (DMACl) in a molar ratio of 0:100 Mineral-based inks
[0081] 100 mg of lead iodide (TCI-Tokyo Chemical Industries) (0.2254 mol) and 0.241 mL of a mixture of dimethylformamide (DMF) (Merck) and dimethyl sulfoxide (DMSO) (Merck) in a ratio of 4:1 (v / v) were introduced into a 4 mL vial: the resulting solution was stirred on a hot plate at a temperature of 60° C. for 10 hours to obtain a first solution. Subsequently, 50 mg of cesium iodide (TCI-Tokyo Chemical Industries) (0.192 mol) and 15.7 mg of dimethylammonium chloride (Merck) (0.192 mol), previously weighed in a 1.5 mL vial, and 0.2138 mL of the first solution were introduced into a 4 mL vial: the resulting solution was stirred on a plate at room temperature (25° C.) for 30 minutes.
[0082] During stirring, precipitation of a yellow solid was noted, which precluded the use of this solution as an ink.
[0083] Example 6 (comparative)
[0084] Preparation of perovskite film using the ink obtained in Example 1
[0085] To this end, the glass substrate was previously subjected to a cleaning step consisting of manual cleaning by wiping with a lint-free cloth soaked in a detergent diluted with deionized water. The substrate was then rinsed with deionized water. Subsequently, the substrate was thoroughly cleaned by the following sequential method: an ultrasonic bath was carried out in (i) deionized water plus detergent (followed by manual drying with a lint-free cloth); (ii) distilled water [followed by manual drying with a lint-free cloth]; (iii) acetone (Aldrich) and (iv) isopropyl alcohol (Aldrich). Specifically, the substrate was placed in a beaker containing the solvent, placed in an ultrasonic bath, kept at room temperature (25°C), and treated for 20 minutes. After treatment (iii) and treatment (iv), the substrate was dried with a compressed nitrogen flow. Subsequently, the substrate was further cleaned by treatment in an ozone device (UV ozone cleaning system - Novasca PSD) before immediately proceeding to the next step.
[0086] The substrate thus treated was ready for the deposition of a perovskite-based ink. For this purpose, 90 mL of the ink obtained in Example 1 were deposited by spin coating at a rotation speed of 3000 rpm (acceleration equal to 1000 rpm / s) for 30 seconds. The whole was then heat-treated (annealed) at 180° C. for the following times: 1 minute, 5 minutes, and 10 minutes. The thickness of the film obtained was found to be 450 nm.
[0087] The thickness was determined by using an atomic force microscope ("TriA AFM" - APE Research) in contact mode with a resolution equal to 256 x 256 pixels on a 20 x 20 m 2 The area was measured by scanning atomic force microscopy.
[0088] exist Figure 2 [angles (2θ) in degrees (°) are shown on the abscissa; counts in arbitrary units (au) are shown on the ordinate], X-ray diffraction patterns were obtained using Cu Kα The diffractograms were acquired using a Brucker D2 Phaser diffractometer with a 0.02° step size and 1 second per step for different durations of heat treatment (annealing). The diffraction pattern obtained after 10 minutes of heat treatment (annealing) highlights the presence of the precursor in the final material, indicating the incompleteness of the reaction.
[0089] Visible absorption spectra (520 nm-800 nm) of the resulting films were also obtained. The spectra were obtained in transmission using a dual beam and double monochromator Perkin Elmer λ1050+ spectrophotometer equipped with dual deuterium and tungsten lamps, a double monochromator and a PbS Peltier photomultiplier tube.
[0090] exist Figure 3[Wavelength in nanometers (nm) is shown on the abscissa; absorbance in arbitrary units (au) is shown on the ordinate], the absorption spectrum of the obtained film in the visible light range (520 nm-800 nm) is shown.
[0091] The photoluminescence spectrum of the obtained film was also obtained. The spectrum was obtained using the optical setup reported in the article by Pica G. et al. in Structural Dynamics (2022), Vol. 9, 011101, doi: 10.1063 / 4.0000134, which consists of a PicoQuant laser excitation source with a wavelength of 470 nm, an interferometer, and a single-photon detector. The measurement was performed by exciting the sample with a laser beam. The photoluminescence emitted by the sample through the lens system was collimated at the input end of the interferometer, and the signal was guided to the single-photon detector through an optical fiber. The photoluminescence spectrum was obtained in the wavelength range of 600 nm to 850 nm.
[0092] exist Figure 4 ] [Wavelength in nanometers (nm) is shown on the abscissa; intensity in arbitrary units (au) is shown on the ordinate], the photoluminescence spectrum (600 nm-850 nm) of the obtained film is shown.
[0093] Example 7 (present invention)
[0094] Preparation of perovskite film using the ink obtained in Example 2
[0095] To this end, 90 mL of the ink obtained in Example 2 were deposited by spin coating for 30 seconds at a rotation speed equal to 3000 rpm (acceleration equal to 1000 rpm / s) on a glass substrate previously subjected to the cleaning step reported in Example 6: the whole was heat-treated (annealed) at 180° C. for the following times: 1 minute, 5 minutes, 10 minutes. The thickness of the film obtained was found to be equal to 450 nm.
[0096] Thickness was measured as reported in Example 6.
[0097] exist Figure 5 In the figure [angles (2θ) in degrees (°) are shown on the abscissa; counts in arbitrary units (au) are shown on the ordinate], the X-ray diffraction patterns obtained for different durations of heat treatment (annealing) as reported in Example 6 are shown. The diffraction pattern obtained after 10 minutes of heat treatment (annealing) shows the presence of limited precursor in the final material, which confirms the correct deposition of the material.
[0098] The absorption spectrum of the film obtained as reported in Example 6 in the visible light range (520 nm - 800 nm) was also obtained. Figure 6In [wavelength in nanometers (nm) is shown on the abscissa; absorbance in arbitrary units (au) is obtained on the ordinate], the absorption spectrum of the obtained film in the visible light range (520 nm-800 nm) is shown.
[0099] The photoluminescence spectra of the resulting films were also obtained as reported in Example 6. Figure 7 ] [Wavelength in nanometers (nm) is shown on the abscissa; intensity in arbitrary units (au) is shown on the ordinate], the photoluminescence spectrum (600 nm-850 nm) of the obtained film is shown.
[0100] Example 8 (present invention)
[0101] Preparation of perovskite film using the ink obtained in Example 3
[0102] To this end, 90 mL of the ink obtained in Example 3 were deposited by spin coating for 30 seconds at a rotation speed equal to 3000 rpm (acceleration equal to 1000 rpm / s) on a glass substrate previously subjected to the cleaning step reported in Example 6. The whole was heat-treated (annealed) at 180° C. for the following times: 1 minute, 5 minutes, 10 minutes. The thickness of the film obtained was found to be equal to 450 nm.
[0103] Thickness was measured as reported in Example 6.
[0104] exist Figure 8 In Figure 6 [angles (2θ) in degrees (°) are shown on the abscissa; counts in arbitrary units (au) are shown on the ordinate], X-ray diffraction patterns are shown for different durations of heat treatment (annealing) as reported in Example 6. The diffraction pattern obtained after 10 minutes of heat treatment (annealing) shows the presence of limited precursor in the final material, which confirms the correct deposition of the material.
[0105] The absorption spectrum of the film obtained as reported in Example 6 in the visible light range (520 nm - 800 nm) was also obtained. Figure 9 In [wavelength in nanometers (nm) is shown on the abscissa; absorbance in arbitrary units (au) is shown on the ordinate], the absorption spectrum of the obtained film in the visible light range (520 nm-800 nm) is shown.
[0106] The photoluminescence spectra of the resulting films were also obtained as reported in Example 6. Figure 10 ] [Wavelength in nanometers (nm) is shown on the abscissa; intensity in arbitrary units (au) is shown on the ordinate], the photoluminescence spectrum (600 nm-850 nm) of the obtained film is shown.
[0107] Example 9 (present invention)
[0108] Preparation of perovskite film using the ink obtained in Example 4
[0109] To this end, 90 mL of the ink obtained in Example 4 were deposited by spin coating for 30 seconds at a rotation speed equal to 3000 rpm (acceleration equal to 1000 rpm / s) on a glass substrate previously subjected to the cleaning step reported in Example 6: the whole was heat-treated (annealed) at 180° C. for the following times: 1 minute, 5 minutes, 10 minutes. The thickness of the film obtained was found to be equal to 450 nm.
[0110] Thickness was measured as reported in Example 6.
[0111] exist Figure 11 In Figure 6 [angles (2θ) in degrees (°) are shown on the abscissa; counts in arbitrary units (au) are shown on the ordinate], X-ray diffraction patterns are shown for different durations of heat treatment (annealing) as reported in Example 6. The diffraction pattern obtained after 10 minutes of heat treatment (annealing) shows the presence of limited precursor in the final material, which confirms the correct deposition of the material.
[0112] The absorption spectrum of the film obtained as reported in Example 6 in the visible light range (520 nm - 800 nm) was also obtained. Figure 12 In [wavelength in nanometers (nm) is shown on the abscissa; absorbance in arbitrary units (au) is shown on the ordinate], the absorption spectrum of the obtained film in the visible light range (520 nm-800 nm) is shown.
[0113] The photoluminescence spectra of the resulting films were also obtained as reported in Example 6. Figure 13 ] [Wavelength in nanometers (nm) is shown on the abscissa; intensity in arbitrary units (au) is shown on the ordinate], the photoluminescence spectrum (600 nm-850 nm) of the obtained film is shown.
[0114] Example 10 (comparative)
[0115] Preparation of perovskite-based solar cells using the ink obtained in Example 1
[0116] For this purpose, a glass substrate (size 29 × 29 × 1.6 mm; sheet resistance equal to 15 Ω / cm) coated with FTO [fluorine-doped tin oxide (SnO2:F)] (Yingkou Shangneng Photoelectric Material Co. Ltd) and patterned was prepared. 2) were prepared on a glass substrate that had previously been subjected to a cleaning step comprising manual cleaning by wiping with a lint-free cloth soaked in a detergent diluted with deionized water. The substrate was then rinsed with deionized water. Subsequently, the substrate was thoroughly cleaned by the following sequential method: an ultrasonic bath was carried out in (i) deionized water plus detergent (followed by manual drying with a lint-free cloth); (ii) distilled water [followed by manual drying with a lint-free cloth]; (iii) acetone (Aldrich) and (iv) isopropyl alcohol (Aldrich). Specifically, the substrate was placed in a beaker containing a solvent, placed in an ultrasonic bath, kept at room temperature (25°C), and treated for 20 minutes. After treatment (iii) and treatment (iv), the substrate was dried with a stream of compressed nitrogen.
[0117] Subsequently, the substrate was further cleaned by treatment in an ozone apparatus (UV ozone cleaning system - Novascan PSD) before proceeding immediately to the next step.
[0118] The substrate thus treated was prepared for the deposition of an electron transport layer (ETL) based on titanium dioxide (TiO 2 ). For this purpose, a solution of titanium (IV) diisopropoxide (Merck) (0.6 mL) and anhydrous isopropanol (Merck) (9 mL) was prepared: the solution was deposited by spray pyrolysis at 450° C. At the end of the deposition, the whole was heat treated (annealed) at 450° C. for 1 hour and then left to cool at room temperature (25° C.). The thickness of the dense layer of titanium dioxide (c-TiO 2 ) was found to be equal to 40 nm.
[0119] A mesoporous titanium dioxide (TiO2) layer was deposited on the titanium dioxide (TiO2) layer obtained as follows. For this purpose, a nanoparticle suspension of mesoporous titanium dioxide (TiO2) (Merck) (1 g) in absolute ethanol (Merck) (8 mL) was prepared: the solution was deposited by spin coating at a rotation speed of 2000 rpm (acceleration of 2000 rpm / s) for 20 seconds. The thickness of the mesoporous titanium dioxide (TiO2) layer was found to be equal to 150 nm. At the end of the deposition, the whole was heat treated (annealed) at 500°C for 20 minutes and then cleaned again by treatment in an ozone device (UV ozone cleaning system - Novascan PSD) before immediately proceeding to the next step.
[0120] On top of the mesoporous titanium dioxide (TiO 2 ) layer thus obtained, a perovskite layer (i.e. 90 μl of the ink obtained in Example 1) was deposited by spin coating at a rotation speed of 3000 rpm (acceleration equal to 1000 rpm / s) for 30 seconds, and the whole was heat-treated (annealed) for 10 minutes at 180° C. The thickness of the perovskite layer was found to be 450 nm.
[0121] A layer based on a hole transport material (hole transport layer—HTL) was deposited on the perovskite layer obtained. For this purpose, 78 mg of spiro-OMeTAD (N 2 ,N 2 ,N 2′ ,N 2′ ,N 7 ,N 7 ,N 7′ ,N 7′ Octa(4-methoxyphenyl)-9,9′-spirobi[9H-fluorene]-2,2′,7,7′-tetramine) (Merck) was dissolved in 1 ml of chlorobenzene (Merck), to which was then added 31 μl of 4-tert-butylpyridine (Merck), 19 μl of a 517 mg / ml stock solution of lithium bis(trifluoromethylsulfonyl)imide (Alfa Aesar) in acetonitrile (Merck), and 14 μl of a 376 mg / ml stock solution of cobalt bis(trifluoromethylsulfonyl)imide (Alfa Aesar) in acetonitrile (Merck). The solution thus obtained was deposited by spin coating at a rotation speed of 4000 rpm (acceleration equal to 2000 rpm / s) for 40 seconds. At the end of the deposition, the whole was left to stand for 12 hours at room temperature (25° C.). The thickness of the layer based on hole transport material (hole transport layer—HTL) was found to be equal to 100 nm.
[0122] A gold (Au) back contact (cathode) with a thickness equal to 80 nm was deposited by vacuum evaporation on said layer based on hole transport material (hole transport layer - HTL), appropriately masking the area of the device in order to obtain an area equal to 0.16 cm 2 effective area.
[0123] The cathode was deposited in a standard vacuum evaporation chamber containing the substrate and an evaporation vessel (Aldrich) equipped with a heating element containing 10 gold (Au) particles (1 mm to 3 mm in diameter). The evaporation process was performed under vacuum at a pressure of approximately 1 × 10 -6 bar. After evaporation, gold (Au) concentrates in the unmasked portions of the device.
[0124] An atomic force microscope (“TriA AFM” - APE Research) was used in contact mode with a resolution of 256×256 pixels at 20×20 μm. 2 Measure the thickness over the area.
[0125] The perovskite-based solar cells thus obtained were electrically characterized at room temperature (25° C.) and 30% humidity (30% RH). The photocurrent was measured by exposing the solar cells to the light of a Sinus-270 solar simulator (AAA grade - Wavelabs), placed at a distance of 36 cm from the solar cells, using an illumination spot equal to 100 mm×100 mm, which provides a solar spectrum of the order AM1.5G and has a power equal to 1 sun (100 mW / cm 2 The simulator is coupled to A 2401 digital multimeter was connected to a personal computer for data collection. The current-voltage density curve (JV) was obtained by measuring the current value in a given voltage range of 100mV to 1200mV. The measurement speed was 100mV / s. The acquisition direction of the curve was changed [reverse scanning, i.e., from JV to JV]. sc V under (short-circuit photocurrent density) oc (open circuit voltage) and forward sweep, i.e. from V oc J at (open circuit voltage) sc (short-circuit photocurrent density)] and keep other acquisition parameters fixed to measure the current value. Table 1 shows the characteristic parameters as average values.
[0126] Light intensity was calibrated using a standard silicon solar cell (Centronic OSD50-0-KG5).
[0127] Table 1
[0128]
[0129] (1) : open circuit voltage;
[0130] (2) : short-circuit photocurrent density;
[0131] (3) : fill factor;
[0132] (4) : Power conversion efficiency.
[0133] Example 11 (present invention)
[0134] Preparation of perovskite-based solar cells using the ink obtained in Example 2
[0135] Perovskite-based solar cells were obtained using the same procedure reported in Example 10, the only difference coming from using the ink obtained in Example 2.
[0136] To this end, 90 μl of the ink obtained in Example 2 were deposited on a mesoporous titanium dioxide (TiO 2 ) layer by spin coating at a rotation speed of 3000 rpm (acceleration equal to 1000 rpm / s) for 30 seconds, and the whole was heat-treated (annealed) for 10 minutes at 180° C. The thickness of the perovskite layer was found to be 450 nm.
[0137] The obtained perovskite-based solar cells were electrically characterized as described above: in Table 2, the characterization parameters are reported as average values.
[0138] Table 2
[0139]
[0140]
[0141] (1) : open circuit voltage;
[0142] (2) : short-circuit photocurrent density;
[0143] (3) : fill factor;
[0144] (4) : Power conversion efficiency.
[0145] Example 12 (present invention)
[0146] Preparation of perovskite-based solar cells using the ink obtained in Example 3
[0147] Perovskite-based solar cells were obtained using the same procedure reported in Example 10, the only difference coming from using the ink obtained in Example 3.
[0148] To this end, 90 μl of the ink obtained in Example 3 were deposited on a mesoporous titanium dioxide (TiO 2 ) layer by spin coating at a rotation speed of 3000 rpm (acceleration equal to 1000 rpm / s) for 30 seconds, and the whole was heat treated (annealed) for 10 minutes at 180° C. The thickness of the perovskite layer was found to be 450 nm.
[0149] The obtained perovskite-based solar cells were electrically characterized as described above: in Table 3, the characterization parameters are reported as average values.
[0150] Table 3
[0151]
[0152] (1) : open circuit voltage;
[0153] (2) : short-circuit photocurrent density;
[0154] (3) : fill factor;
[0155] (4) : Power conversion efficiency.
[0156] Example 13
[0157] Preparation of perovskite-based solar cells using the ink obtained in Example 4
[0158] Perovskite-based solar cells were obtained using the same procedure reported in Example 10, the only difference coming from using the ink obtained in Example 4.
[0159] To this end, 90 μl of the ink obtained in Example 2 were deposited on a mesoporous titanium dioxide (TiO 2 ) layer by spin coating at a rotation speed of 3000 rpm (acceleration equal to 1000 rpm / s) for 30 seconds, and the whole was heat-treated (annealed) for 10 minutes at 180° C. The thickness of the perovskite layer was found to be 450 nm.
[0160] The obtained perovskite-based solar cells were electrically characterized as described above: in Table 4, the characteristic parameters are reported as average values.
[0161] Table 4
[0162]
[0163] (1) : open circuit voltage;
[0164] (2) : short-circuit photocurrent density;
[0165] (3) : fill factor;
[0166] (4) : Power conversion efficiency.
Claims
1. A method for preparing a perovskite-based ink, wherein the perovskite has the general formula (I): CsPbI 3-y Br y (I) wherein y is a number from 0 to 0.2, preferably from 0.05 to 0.1; Includes the following step: (a) dissolving lead iodide (PbI2) in at least one organic solvent to obtain a first solution, wherein the at least one organic solvent is selected from dimethyl sulfoxide (DMSO), dimethylformamide (DMF), γ-butyrolactone (GBL) or a mixture thereof, preferably dimethyl sulfoxide (DMSO), dimethylformamide (DMF) or a mixture thereof; (b) dissolving cesium iodide (CsI) and at least one ammonium salt having the general formula (II) in a portion of the first solution obtained in step (a) to obtain a second solution: R x H 4-x NI(II) wherein R represents a linear or branched C1-C4 alkyl group, preferably a methyl group, and x is an integer from 2 to 4, preferably 2; (c) dissolving cesium iodide (CsI) and at least one ammonium salt having the general formula (III) in a portion of the first solution obtained in step (a) to obtain a third solution: R x H 4-x NBr(III) wherein R represents a linear or branched C1-C4 alkyl group, preferably a methyl group, and x is an integer from 2 to 4, preferably 2; (d) mixing the second solution obtained in step (b) with the third solution obtained in step (c) to obtain a perovskite-based ink; Characterized in that, in the step (d), the molar ratio of the at least one ammonium salt having the general formula (II) to the at least one ammonium salt having the general formula (III) is 0:100 to 50:
50.
2. The method for preparing a perovskite-based ink according to claim 1, wherein the at least one ammonium salt having the general formula (II) is dimethylammonium iodide (DMAI).
3. The method for preparing a perovskite-based ink according to claim 1 or 2, wherein the at least one ammonium salt having the general formula (III) is dimethylammonium bromide (DMABr).
4. The method for preparing a perovskite-based ink according to any one of the preceding claims, wherein step (a) is performed under the following conditions: - at a temperature of 30°C to 80°C, preferably 40°C to 70°C; and / or - for a period of 1 to 12 hours, preferably 4 to 11 hours.
5. The method for preparing a perovskite-based ink according to any one of the preceding claims, wherein step (b) is performed under the following conditions: - at a temperature of 15°C to 35°C, preferably 20°C to 30°C, more preferably at room temperature (25°C); and / or - for a period of 5 minutes to 2 hours, preferably 10 minutes to 1 hour.
6. The method for preparing a perovskite-based ink according to any one of the preceding claims, wherein step (c) is performed under the following conditions: - at a temperature of 15°C to 35°C, preferably 20°C to 30°C, more preferably at room temperature (25°C); and / or - for a period of 5 minutes to 2 hours, preferably 10 minutes to 1 hour.
7. The method for preparing a perovskite-based ink according to any one of the preceding claims, wherein step (d) is performed under the following conditions: - at a temperature of 15°C to 35°C, preferably 20°C to 30°C, more preferably at room temperature (25°C); and / or - for a period of 5 minutes to 2 hours, preferably 8 minutes to 1 hour.
8. A method for preparing a perovskite film, comprising the following steps: (i) depositing the perovskite-based ink obtained by the method according to any one of the preceding claims on a substrate to form a film; (ii) The substrate is heat treated (annealed) at a temperature of 120°C to 190°C, preferably 135°C to 185°C.
9. A method for preparing a perovskite-based photovoltaic cell (or solar cell), comprising the following steps: (a1) preparing a glass substrate covered with a transparent conductive oxide layer (transparent conductive oxide-TCO) (anode); (b1) Deposition of a layer based on an electron transport material (electron transport layer - ETL); (c1) optionally, depositing a layer based on a mesoporous oxide (scaffold) on the layer based on an electron transport material (electron transport layer - ETL) obtained in step (b1); (d1) depositing the perovskite-based ink obtained by the method according to any one of claims 1 to 7 on the layer based on electron transport material (electron transport layer - ETL) obtained in step (b1), or on the layer based on mesoporous oxide (scaffold) obtained in step (c1), to obtain a photoactive layer; (e1) depositing a layer based on a hole transport material (hole transport layer - HTL) on the photoactive layer obtained in step (d1); (f1) depositing a metal contact constituting the cathode (back contact) on the layer based on a hole transport material (hole transport layer—HTL) obtained in step (e1); Wherein said step (d1) is carried out at a temperature of 120°C to 190°C, preferably 135°C to 185°C.